Construct of QC-LDPC codes based on Z-shape and arithmetic progression sequence - Zhang, Li-Li; Zhao, Ze-Mao; Bao, Jian-Rong (Tongxin Xuebao, 2010)
For the issue of determining cyclic shift coefficients of the quasi-cyclic sub-matrix in the quasi-cyclic low density parity check, a method was presented based on Z-shape and arithmetic progression sequence to compute the cyclic shift coefficients. By this method, cyclic shift coefficients could be expressed in simple analytic expressions, and cycles of length four in parity matrix were eliminated. Simulations show that, under the classing BP decoding algorithm, the SNR of the LDPC codes with the proposed algorithm is better than the LDPC codes in DVB-S2 close to 0.4 dB at the BER performance of 10(-4). Futhermore, the BER performance of the new codes is no less than the Mackay random codes under the same conditions.